The Temporal Bone : Anatomical Dissection and Surgical Approaches. - Sanna, Mario (Thieme Medical Publishers, Incorporated, 2018)
Temporal bone anatomy is arguably the most complex anatomy in the human body. The proximity of vital neural and vascular structures, the intricate three-dimensional relationships involved, and the manner in which these structures are encased in a labyrinth of bony canals pose a major challenge to the preparation for and performance of surgery. It follows that specialized anatomy teaching courses are indispensable, and these are most effective when executed with the help of dissections on cadaver preparations. Mario Sanna's Temporal Bone is a guide to the dissection courses that the author hims.